Teat-apex colonizer Bacillus from healthy cows antagonizes mastitis-causing Staphylococcus aureus biofilms - Isaac, Paula (2023)
Staphylococcus aureus is the most frequent causal agent of bovine mastitis, which is largely responsible for milk production losses worldwide. The pathogen's ability to form stable biofilms facilitates intramammary colonization and may explain disease persistence. This virulence factor is also highly influential in the development of chronic intramammary infections refractory to antimicrobial therapy, which is why novel therapies that can tackle multiple targets are necessary. Since udder microbiota have important implications in mastitis pathogenesis, they offer opportunities to develop alternative prophylactic and therapeutic strategies. Here, we observed that a Bacillus strain from the teat apex of lactating cows was associated to reduce colonization by S. aureus. The strain, identified as Bacillus sp. H21, was able to antagonize in-formation or mature S. aureus biofilms associated to intramammary infections without affecting cell viability. When exploring the metabolite responsible for this activity, we found that a widespread class of Bacillus exopolysaccharide, levan, eliminated the pathogenic biofilm under evaluated conditions. Moreover, levan had no cytotoxic effects on bovine cellular lines at the biologically active concentration range, which demonstrates its potential for pathogen control. Our results indicate that commensal Bacillus may counteract S. aureus-induced mastitis, and could therefore be used in novel biotechnological strategies to prevent and/or treat this disease.